Inorganic material as well as preparation method and application thereof
By developing hexagonal crystal phase iridium oxide nanomaterials as catalysts, the problem of low catalytic activity of the existing anode catalyst for PEM electrolytic water is solved, lower overpotential of oxygen evolution reaction and lower catalyst loading are achieved, and the efficiency and stability of PEM hydrogen production technology are improved.
Patent Information
- Application Number
- CN202311127335.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
AI Technical Summary
The existing anode catalysts for PEM electrolytic water have low catalytic activity, resulting in a high overpotential of the oxygen evolution reaction and a large amount of precious metal iridium, which limits the large-scale application of PEM hydrogen production technology.
An inorganic material including hexagonal crystal phase iridium oxide nanomaterial was developed. The material was prepared by microwave reaction, with high intrinsic catalytic activity and acid resistance, and could effectively reduce the overpotential of the oxygen evolution reaction in an acidic environment.
The catalytic activity of the anode catalyst is improved, the overpotential of the oxygen evolution reaction is reduced, the load of the catalyst is reduced, the cost is reduced, and the operation efficiency and stability of the PEM hydrogen production technology are improved.
Smart Images

Figure CN119528233A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the field of electrocatalysis technology, and specifically to an inorganic material and a preparation method and application thereof. Background Art
[0002] Hydrogen production by water electrolysis is the main method for preparing renewable hydrogen energy. Among them, proton exchange membrane (PEM) water electrolysis hydrogen production technology is considered to be a hydrogen production technology with higher practical value compared to alkaline water electrolysis hydrogen production technology because of its advantages such as high working current density, high energy conversion efficiency and high purity of hydrogen produced.
[0003] Because the kinetic reaction rate of the oxygen evolution reaction on the anode side is slower than that of the hydrogen evolution reaction on the cathode side during water electrolysis, an anode catalyst is needed to reduce the overpotential of the oxygen evolution reaction. Since the anode catalyst of the PEM electrolysis device is in an acidic environment of local proton exchange, the anode catalyst suitable for PEM water electrolysis technology should be able to be used stably in an acidic environment. At present, the anode catalyst used in commercial PEM electrolysis devices is generally metal iridium and / or its oxides with good acid resistance, but the catalytic activity of iridium-based catalysts for oxygen evolution reaction still needs to be improved. The amount of iridium used on the anode side is large, and the amount of precious metal element iridium used is also correspondingly large, which limits the large-scale application of PEM hydrogen production technology. Therefore, the development of iridium-based oxygen evolution catalysts with higher catalytic activity is crucial to improving the operating efficiency of PEM hydrogen production technology and reducing the cost of hydrogen production. Summary of the invention
[0004] In view of this, the embodiments of the present application provide an inorganic material and a preparation method and application thereof to solve the problem of low catalytic activity of the anode catalyst for existing PEM water electrolysis.
[0005] A first aspect of an embodiment of the present application provides an inorganic material, wherein the inorganic material includes an iridium oxide nanomaterial, and the iridium oxide nanomaterial has a hexagonal crystal phase structure.
[0006] The inorganic material includes a hexagonal iridium oxide nanomaterial. Compared with the commercial IrO2 catalyst used for water electrolysis, the hexagonal crystal phase structure can make the intrinsic catalytic activity of the inorganic material higher, the effect of reducing the overpotential of the oxygen evolution reaction is more obvious, and the loading capacity can be reduced, which is conducive to reducing costs.
[0007] In the embodiment of the present application, the crystal structure of the iridium oxide nanomaterial includes iridium oxide octahedrons, and the iridium oxide octahedrons are connected to form the hexagonal crystal structure. At this time, the inorganic material containing the iridium oxide nanomaterial is more resistant to large current and has good stability when used as an anode catalyst for electrolysis of water.
[0008] In the embodiment of the present application, the iridium oxide nanomaterial has two crystal planes with an angle of 59.5°-60.5°, which can reflect to a certain extent that the iridium oxide nanosheet of the present application has a hexagonal crystal structure.
[0009] In the embodiment of the present application, the XRD spectrum of the inorganic material has crystal plane diffraction peaks at 2θ of 32.9°-33.9° and 35.5°-36.5°. These crystal plane diffraction peaks are unique to the hexagonal iridium oxide nanomaterial of the embodiment of the present application.
[0010] In the embodiment of the present application, the inorganic material contains a single crystal iridium oxide nanomaterial in the hexagonal crystal structure. The single crystal iridium oxide nanomaterial has good electronic properties, better catalytic performance, and better acid resistance and stability.
[0011] In the embodiment of the present application, the iridium oxide nanomaterial comprises iridium oxide nanosheets. The nanosheet-shaped iridium oxide material has a large specific surface area and active area, thereby making the catalytic activity of the above-mentioned inorganic material higher. Among them, a single iridium oxide nanosheet is formed by stacking multiple atomic layer-level sheets.
[0012] In the embodiment of the present application, the thickness of the iridium oxide nanosheet is 0.2-50 nm, and the lateral size of the iridium oxide nanosheet is 0.01 μm-10 μm.
[0013] In the embodiment of the present application, at least a plurality of the iridium oxide nanomaterials are assembled into a three-dimensional cluster structure. The three-dimensional cluster structure generally has certain gaps, which can ensure that there are open and larger atomic surfaces between the iridium oxide nanomaterials, thereby making the specific surface area of the inorganic material larger and the catalytic performance better.
[0014] In the embodiment of the present application, the average particle size of the three-dimensional cluster structure is 0.03 μm-20 μm.
[0015] In the embodiment of the present application, the specific surface area of the inorganic material is 50-100m 2 The specific surface area of the inorganic material containing iridium oxide nanosheets is much larger than that of the commercial IrO2 catalyst, and the catalytic utilization rate is high, thereby reducing the cost of the catalyst while improving the catalytic activity.
[0016] In the embodiment of the present application, the loading amount of the inorganic material on the working electrode in the three-electrode electrolytic cell is 0.1-1 mg / cm 2 , current density is 10mA / cm 2 Under the conditions of , the overpotential of the inorganic material is below 240 mV. The lower overpotential reflects that the catalytic performance of the inorganic material is better.
[0017] A second aspect of the embodiment of the present application provides a method for preparing an inorganic material, comprising the following steps:
[0018] Placing a reaction material comprising a solid alkali metal hydroxide and a solid iridium salt in a microwave reaction device for microwave reaction to obtain a reaction material; wherein the product of the power in watts and the reaction time in minutes in the microwave reaction is in the range of 3000-30000;
[0019] The obtained reaction materials are dispersed in water, and solids are obtained by solid-liquid separation. The obtained solidified material is an inorganic material; wherein the inorganic material comprises iridium oxide nanomaterial, and the iridium oxide nanomaterial has a hexagonal crystal phase structure.
[0020] In the above preparation method, by subjecting alkali metal hydroxide and iridium salt to a solid phase melting reaction under a specific microwave, a hexagonal iridium oxide nanomaterial can be obtained, which has a high intrinsic catalytic activity. The preparation method is simple to operate, takes a short time, and is easy to prepare on a large scale.
[0021] In the embodiment of the present application, the power of the microwave reaction is 500-1000 W, and the reaction time is 5-60 min. Under the condition that the power and time product of the microwave reaction are satisfied, the power and time of the microwave reaction are controlled within this range, which can better ensure the obtaining of a nano-sheet iridium oxide material with a single crystal structure, and its catalytic activity is higher.
[0022] In the embodiment of the present application, the molar ratio of the alkali metal hydroxide to the iridium element in the iridium salt is (100-5000): 1. This ensures good dispersibility of the iridium salt in the molten potassium hydroxide, maintains a suitable product generation reaction concentration, and ensures that the obtained iridium oxide is in the form of hexagonal nanosheets.
[0023] In the embodiment of the present application, the alkali metal hydroxide is potassium hydroxide. KOH has a strong ability to absorb microwave energy, which is very helpful for ensuring the dispersibility of iridium salt in its molten state and the smooth crystallization and synthesis of iridium oxide nanosheets.
[0024] The third aspect of the embodiments of the present application provides a catalyst, which includes the inorganic material described in the first aspect of the embodiments of the present application or the inorganic material prepared by the preparation method described in the second aspect of the embodiments of the present application, and the catalyst also includes a binder.
[0025] The fourth aspect of the embodiments of the present application provides the application of the inorganic material described in the first aspect of the embodiments of the present application and the catalyst described in the third aspect of the embodiments of the present application in fuel cells, water electrolysis, and other electrochemical technologies.
[0026] The inorganic material or catalyst may be used in the anode catalyst layer in the water electrolysis or in the anode catalyst layer of the fuel cell.
[0027] The fifth aspect of the embodiment of the present application provides a membrane electrode, the membrane electrode comprising a proton exchange membrane, and an anode catalyst layer and a cathode catalyst layer disposed on opposite sides of the proton exchange membrane, wherein the anode catalyst layer comprises the inorganic material described in the first aspect of the embodiment of the present application or the catalyst described in the third aspect of the embodiment of the present application. The membrane electrode can be used in a fuel cell, a water electrolysis device or other electrochemical devices.
[0028] When the iridium element loading derived from the inorganic material in the membrane electrode is low, the inorganic material or catalyst provided in the embodiments of the present application can still exhibit excellent electrocatalytic activity and stability.
[0029] A sixth aspect of an embodiment of the present application provides a water electrolysis device, which includes the membrane electrode described in the fifth aspect of the present application, and a gas diffusion layer and a bipolar plate current collector are stacked in sequence on opposite sides of the membrane electrode.
[0030] By using the inorganic material provided in the embodiment of the present application as an anode catalyst of a water electrolysis device, when the inorganic material has a lower loading, the decomposition voltage of the water electrolysis device when electrolyzing water at the same temperature and current density can be lower. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic diagram of the structure of a PEM water electrolysis device provided in an embodiment of the present application.
[0032] Figure 2 This is a scanning electron microscope photograph of the inorganic material prepared in Example 1 of the present application.
[0033] Figure 3 This is a transmission electron microscope photograph of the inorganic material prepared in Example 1 of the present application.
[0034] Figure 4 The high-angle annular dark field scanning transmission image of a single iridium oxide nanosheet in the inorganic material prepared in Example 1 of the present application and its selected area electron diffraction pattern map (Figure a), the spherical aberration electron microscope image of a single iridium oxide nanosheet (Figure b), and the crystal structure model image of a single iridium oxide nanosheet (Figure c).
[0035] Figure 5 This is the X-ray diffraction spectrum of the inorganic material prepared in Example 1 of the present application.
[0036] Figure 6 This is a test chart of nitrogen adsorption specific surface area of the inorganic material prepared in Example 1 of the present application.
[0037] Figure 7 This is a graph showing the polarization test results of the three-electrode oxygen evolution reaction of the inorganic material prepared in Example 1 of the present application.
[0038] Figure 8 This is a polarization test curve of the inorganic material prepared in Example 1 of the present application as an anode catalyst for a PEM water electrolysis device.
[0039] Fig. 9 This is the electrochemical stability curve of the inorganic material prepared in Example 1 of the present application as the anode catalyst of the PEM water electrolysis device.
[0040] Fig.10 This is a scanning electron microscope photograph of the inorganic material prepared in Example 4 of the present application.
[0041] Fig.11 This is a scanning electron microscope photograph of the inorganic material prepared in Example 6 of the present application.
[0042] Fig.12 This is a scanning electron microscope photograph of the inorganic material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0043] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.
[0044] The electrochemical reactions involved in PEM water electrolysis technology include the hydrogen evolution reaction (HER) on the cathode and the oxygen evolution reaction (OER) on the anode, as shown below: + +4e - =2H2(HER); 2H2O=O2+4H + +4e - (OER); the overall reaction is: 2H2O=O2+2H2. In the two half reactions, the reaction rate of OER is slow, and the anode side is in an acidic environment. In order to improve the electrochemical efficiency of water electrolysis, finding an anode oxygen evolution catalyst with good acid resistance and high catalytic activity to reduce the overpotential of the anode oxygen evolution reaction has become the main challenge for the industrial application of water electrolysis technology.
[0045] The schematic diagram of the structure of the water electrolysis device commonly used in PEM water electrolysis technology is as follows Figure 1 As shown. The water electrolysis device 100 includes a membrane electrode 10, and the membrane electrode 10 includes a proton exchange membrane 11, and an anode catalyst layer 12 and a cathode catalyst layer 13 located on opposite sides of the proton exchange membrane 11. The anode catalyst layer 12 and the cathode catalyst layer 13 of the membrane electrode 10 are also sequentially stacked with a gas diffusion layer and a bipolar plate current collector. Among them, the anode catalyst layer 12 contains an anode catalyst for reducing the overpotential of the anode oxygen evolution reaction, and the cathode catalyst layer 13 contains a cathode catalyst for reducing the overpotential of the cathode hydrogen evolution reaction. The embodiment of the present application provides an inorganic material with high catalytic activity that can be used in the anode catalyst layer 12.
[0046] Specifically, the inorganic material provided in the embodiment of the present application includes an iridium oxide nanomaterial, and the iridium oxide nanomaterial has a hexagonal crystal structure. The "hexagonal crystal structure" may include a conventional hexagonal crystal structure or a distorted hexagonal crystal structure in which the crystal structure is distorted to a certain extent due to the atomic stacking method.
[0047] The inorganic material provided by the present application includes a hexagonal iridium oxide nanomaterial. Compared with the commercial IrO2 catalyst (tetragonal nanoparticles) used for water electrolysis, the intrinsic catalytic activity of the iridium oxide nanomaterial with a hexagonal crystal structure is higher, so that the catalytic activity of the inorganic material is higher, and the overpotential of the oxygen evolution reaction of water electrolysis can be lowered; because the catalytic activity of the inorganic material is higher, its loading in the membrane electrode can be lower, which is conducive to reducing costs. Under the condition of the same loading of the catalyst on the membrane electrode and the same current density of water electrolysis, the inorganic material provided by the embodiment of the present application can reduce the overpotential of the oxygen evolution reaction to a lower level; when the electrolysis potential of the oxygen evolution reaction is reduced to the same potential, the amount of the inorganic material in the embodiment of the present application can be lower and the efficiency of reducing the overpotential is higher. In addition, iridium oxide has good corrosion resistance in an acidic environment and can stably exert catalytic performance in the oxygen evolution reaction of PEM water electrolysis. Therefore, the inorganic material has good durability and long service life.
[0048] Therefore, the above-mentioned inorganic material provided in the embodiment of the present application can solve the problems of low catalytic activity and high dosage of precious metal Ir in the existing anode catalyst for PEM water electrolysis.
[0049] In an embodiment of the present application, in the iridium oxide nanomaterial, there are at least two crystal planes with an angle of 59.5°-60.5°. This can be learned from the HAADF-STEM image of the iridium oxide nanomaterial. In the HAADF-STEM image of the iridium oxide nanomaterial, there are two crystal planes with an angle of 59.5°-60.5°, which can reflect to a certain extent that the iridium oxide nanomaterial of the present application has a hexagonal crystal phase structure. In some embodiments of the present application, in the iridium oxide nanomaterial, there are two crystal planes with an angle of 60°. In some embodiments, in the iridium oxide nanomaterial, the angle between adjacent crystal planes is 60°, for example The angle between any two is 60°. It should be noted that, due to the limitation of the detection instrument, the angle value of the crystal plane in the embodiment of the present application may have a detection error allowed by the detection instrument or detection method in the field. These detection errors should also be included in the protection scope required by the present application.
[0050] In the implementation mode of the present application, the diffraction bright spots around the transmission spot at the exact center in the selected area electron diffraction pattern of a single iridium oxide nano material are measured and analyzed for calibration, and it is learned that the geometric shape of the basic unit expressing the symmetry of the diffraction pattern is a regular hexagon, and the crystal face index and crystal reciprocal lattice of the diffraction points constituting the regular hexagon conform to the hexagonal crystal phase structure. The calibration result of the selected area electron diffraction pattern of the iridium oxide nano material is consistent with the crystal face index of the hexagonal crystal phase structure. This further proves that the iridium oxide nano material of the present application is a hexagonal crystal phase structure.
[0051] In the implementation manner of the present application, the iridium oxide nano material comprises an iridium oxide octahedron in its crystal structure, and the iridium oxide octahedron is connected with each other in a common edge, and is orderly expanded into the hexagonal crystalline phase structure. At this time, when the inorganic material containing the iridium oxide nano material is used as an anode catalyst for electrolysis of water, it can withstand a larger current and has better stability. Wherein, the above-mentioned crystal structure characteristics can be learned from the crystal structure simulation diagram of the iridium oxide nano material, and the iridium oxide nano material is a hexagonal Bragg unit cell. In addition, the theoretical interlayer spacing of the nano-sheet iridium oxide nano material learned based on the crystal structure simulation diagram is about 0.69nm, which is consistent with the experimental test results of subsequent XRD.
[0052] In the implementation manner of the present application, in the XRD spectrum of the inorganic material, there are crystal plane diffraction peaks at 2θ of 32.9°-33.9° and 35.5°-36.5°. These crystal plane diffraction peaks are crystal plane diffraction peaks unique to the hexagonal phase of the iridium oxide nanomaterial in the embodiment of the present application, which are different from the tetragonal phase of the iridium oxide material. It should be noted that, limited by the detection method or detection instrument, the 2θ angle value of the diffraction peak in the embodiment of the present application may have detection errors allowed by the detection instrument or detection method in the field. These detection errors should also be included in the protection scope required by the present application. In some examples of the present application, in the XRD spectrum of the inorganic material, there are crystal plane diffraction peaks at 2θ of 33.4° and 36°.
[0053] In the present embodiment, there is a single crystal iridium oxide nano material in a hexagonal phase in the inorganic material. The iridium oxide nano material with a single crystal structure has good electronic properties and better catalytic performance than polycrystalline materials due to its low grain boundary resistance, and its acid resistance and stability are better. Among them, the single crystal structure can be obtained by calibrating the selected area electron diffraction pattern of a single iridium oxide nano material. The geometric feature of the selected area electron diffraction pattern of the iridium oxide nano material with a single crystal structure is a spot pattern. In some embodiments of the present application, the iridium oxide nano materials are all single crystal structures in a hexagonal phase.
[0054] In the embodiment of the present application, the iridium oxide nano material comprises iridium oxide nano sheets. That is, the morphology of the iridium oxide nano material comprises nano sheets. The specific surface area and active area of the nano sheet-like iridium oxide nano material are large, and its catalytic activity is high, thereby making the catalytic activity of the above-mentioned inorganic material better. In the embodiment of the present application, a single iridium oxide nano sheet can be formed by stacking a plurality of atomic layer-level sheets in sequence. Wherein, the stacking direction of each sheet is parallel to the thickness direction of each sheet.
[0055] In the present application, the thickness of the iridium oxide nanosheet is less than the lateral dimension of the iridium oxide nanosheet. Wherein, "lateral dimension" refers to the dimension perpendicular to the thickness direction of the iridium oxide nanosheet. For example, for a nanosheet with a quadrilateral cross-sectional shape, the lateral dimension may include the length and width of the cross-sectional shape; for a nanosheet with a circular cross-sectional shape, the lateral dimension refers to the diameter of the circle; when the cross-sectional shape is a polygon (such as a hexagon), the lateral dimension may refer to the diameter of the circumscribed circle of the polygon.
[0056] In the embodiment of the present application, the thickness of the iridium oxide nanosheet is 0.2-50nm, for example, specifically 0.5nm, 1nm, 2nm, 3nm, 5nm, 6nm, 8nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, etc. In some embodiments, the thickness of the iridium oxide nanosheet is 0.2-10nm. When the thickness of the iridium oxide nanosheet is thin, it can ensure that the sum of the specific surface areas of the inorganic material on the membrane electrode is high, which is conducive to the improvement of catalytic activity.
[0057] In the embodiment of the present application, the lateral size of the iridium oxide nanosheet is 0.01 μm-10 μm, for example, specifically 0.02 μm, 0.03 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, etc. In some embodiments, the lateral size of the iridium oxide nanosheet is 0.5 μm-10 μm. The lateral size of the iridium oxide nanosheet is at the micron level, which can provide more active surfaces and is conducive to the improvement of its catalytic activity.
[0058] In the embodiment of the present application, the inorganic material includes a three-dimensional cluster structure, and the three-dimensional cluster structure is assembled by several iridium oxide nano materials. There are generally gaps in the three-dimensional cluster structure, and the presence of the gap can further increase the specific surface area of the inorganic material and improve its electrocatalytic performance. In some embodiments, the three-dimensional cluster structure is assembled by several iridium oxide nano sheets. This can effectively avoid the mutual stacking between nano sheets, which is conducive to ensuring that there is an open and larger atomic surface between the nano sheets, and there are generally gaps in the three-dimensional cluster structure. The presence of the gap and the multiple iridium oxide nano sheets constituting the three-dimensional cluster structure can further increase the specific surface area of the inorganic material, and facilitate the entry of the reactant (water to be electrolyzed), thereby improving its catalytic ability to the reactant, and is conducive to the membrane electrode prepared by the inorganic material to show good electrocatalytic performance. In the present application, the inorganic material can be a three-dimensional cluster structure assembled by the iridium oxide nano sheets, or it can simultaneously contain iridium oxide nano sheets and the three-dimensional cluster structure. In some embodiments, the inorganic material is a three-dimensional cluster structure, which is assembled by several iridium oxide nano sheets.
[0059] In the embodiment of the present application, the average particle size of the three-dimensional cluster structure is 0.03 μm-20 μm. The particle size refers to the maximum cross-sectional width of the three-dimensional cluster structure, that is, the maximum lateral dimension (the distance between the two points with the largest dimension on the cross section). For a spherical or quasi-spherical cluster structure, the particle size refers to the diameter of its cross section; for a polygonal cross section, the particle size is the diameter of the circumscribed circle of the polygon.
[0060] In the embodiment of the present application, the specific surface area of the inorganic material is 50-100m 2 / g. The specific surface area can be measured by nitrogen adsorption method (also known as "BET method"). Compared with the currently commercially available IrO2 catalyst, the inorganic material containing iridium oxide nanomaterial provided in the embodiment of the present application has a larger specific surface area (the former is generally 10-20m 2 / g), which increases the active sites and can greatly improve the utilization rate of the catalyst, thereby improving the catalytic activity while reducing the cost of the catalyst. In some embodiments, the specific surface area of the inorganic material is 75-100m 2 / g, for example, 78, 80, 82, 85, 88, 90, 95 or 98m 2 / g, etc.
[0061] In some embodiments of the present application, the mass percentage of the iridium oxide in the inorganic material is 100%. That is, the inorganic material is composed only of iridium oxide nanosheets. In this case, the catalytic stability of the inorganic material is higher.
[0062] In another embodiment of the present application, the inorganic material further comprises one or more of platinum oxide and ruthenium oxide. The inorganic material may contain platinum oxide nanomaterials and ruthenium oxide nanomaterials; or the iridium oxide nanomaterial (such as iridium oxide nanosheets) may contain one or more of platinum oxide and ruthenium oxide. Furthermore, in the inorganic material, the mass percentage of the iridium oxide is at least 50%, for example, 50-95%.
[0063] The present application also provides a method for preparing the above inorganic material. Specifically, the preparation method comprises the following steps:
[0064] (1) subjecting a reaction material comprising a solid alkali metal hydroxide and a solid iridium salt to a microwave reaction in a microwave reaction device to obtain a reaction material; wherein the product of the power in watts and the reaction time in minutes in the microwave reaction is in the range of 3000-30000;
[0065] (2) adding water to disperse the obtained reaction materials, and performing solid-liquid separation to obtain a solid, wherein the obtained solidified material is an inorganic material; wherein the inorganic material comprises an iridium oxide nanomaterial, and the iridium oxide nanomaterial has a hexagonal crystal phase structure.
[0066] In the above preparation method, the reaction raw materials - alkali metal hydroxide and iridium salt interact with microwaves to produce molecular polarization, orientation, friction, collision, etc., thereby absorbing microwave energy and producing a certain thermal effect. The specific product of the power and time of the above microwave reaction can ensure that the solid alkali metal hydroxide and the solid iridium salt slowly melt and react, and finally crystallize to form an iridium oxide nanomaterial with a hexagonal phase, and its intrinsic catalytic activity is high, which can show excellent catalytic activity compared with commercial iridium oxide catalysts.
[0067] The above preparation method uses a microwave-assisted high-temperature solid-phase melting preparation strategy, which has a simple process, is easy to operate, and is suitable for large-scale preparation. Compared with the traditional hydrothermal method, this preparation method takes less time, consumes less energy, and has a high yield and high purity of the product.
[0068] In the embodiment of the present application, the product of the power and time of the microwave reaction is in the range of 3000-24000W·min, and can further be in the range of 5000-24000W·min, for example, specifically 5000, 6000, 8000, 10000, 12000, 15000, 18000, 20000 or 24000W·min, etc. Further, in the embodiment of the present application, in step (1), the power of the microwave reaction is 500-1000W, and the reaction time can be 5-60min. Wherein, the power of the microwave reaction is controlled to be below 1000W, which can ensure that the iridium salt melts slowly, and the iridium oxide material obtained by the reaction is in the form of flakes rather than particles, and the catalytic activity is higher. Specifically, the power of the microwave reaction can be 600W, 650W, 700W, 750W, 800W, 850W, 9000W, 950W, 980W, etc. The reaction time of the microwave reaction can be 10 min, 20 min, 30 min, 40 min, 45 min, 50 min, etc. In some embodiments of the present application, the microwave reaction can be carried out under a constant microwave power, which can ensure a higher yield of the iridium oxide material.
[0069] In step (1), the above-mentioned reaction raw materials do not include liquid solvents. The reaction raw materials containing solid alkali metal hydroxides and solid iridium salts can be placed in a corrosion-resistant microwave reaction container (such as a silicon carbide crucible) and then placed in a microwave reaction device. Wherein, the iridium salt is a salt containing iridium element, including but not limited to iridium chloride (such as IrCl3·3H2O, IrCl4), iridium acetate, iridium nitrate, (hydrated) potassium chloroiridate, (hydrated) sodium chloroiridate, etc. One or more. The alkali metal hydroxide may include one or more of potassium hydroxide (KOH), sodium hydroxide (NaOH), lithium hydroxide (LiOH), rubidium hydroxide (RbOH), etc. In some embodiments of the present application, the alkali metal hydroxide is KOH. KOH has a strong absorption capacity for microwave energy, which facilitates its own absorption of microwave energy and melting. It can also act as a certain "solvent" to help the iridium salt continue to melt slowly, thereby ensuring the smooth crystallization and synthesis of hexagonal iridium oxide nanomaterials.
[0070] In step (1), the molar ratio of the alkali metal hydroxide to the iridium element in the iridium salt is (100-5000): 1. When the relationship between the power and time of the microwave reaction satisfies the above conditions, controlling the molar ratio of the two reaction raw materials within this range can further ensure the good dispersibility of the iridium salt in the molten potassium hydroxide, maintain a suitable product generation reaction concentration, and control the orientation and speed of the iridium oxide crystal growth, ensuring that the obtained iridium oxide is in the form of hexagonal nanosheets rather than granules. In some embodiments, the molar ratio of the alkali metal hydroxide to the iridium element in the iridium salt is (400-1500): 1.
[0071] In some embodiments of the present application, the reaction raw materials in step (1) may also include one or more of a platinum source and a ruthenium source. The platinum source and the ruthenium source may be chlorides, chlorates, nitrates, etc. of platinum or ruthenium. Accordingly, the prepared inorganic material may contain platinum oxide and / or ruthenium oxide.
[0072] After the microwave reaction is completed, the microwave reaction equipment is cooled naturally to room temperature, or more precisely, the microwave reaction container containing the reaction material is cooled naturally to room temperature, and then the reaction material is post-treated. In step (2), the obtained reaction material is dispersed with water to dissolve the unreacted reaction raw materials (especially the excess alkali metal hydroxide), and then solid-liquid separation is performed to obtain a solid, which includes the desired inorganic material.
[0073] In addition, the solid can also be purified as follows: the solid is washed several times and the solid-liquid is separated to obtain a purified solid. Finally, the solid can be dried and stored for later use. Among them, the solid-liquid separation can be centrifugation, suction filtration, etc. The washing in the purification process can be all deionized water washing, or multiple deionized water washings can be performed first, and then multiple anhydrous ethanol washings. In addition, after the purification process, the purified solid can also be dried. Among them, the specific treatment method of the drying process is not limited, for example, it can be a vacuum drying process, or a room temperature drying process, or a combination of the two. In some embodiments, the drying process is specifically a constant temperature vacuum drying process at 30-60°C in a vacuum heating oven, and the treated product is dried and stored at room temperature for later use.
[0074] The above-mentioned preparation method provided in the present application prepares inorganic materials by means of a microwave-assisted high-temperature solid-phase melting reaction. The operation is simple, time-saving, and easy to prepare in large quantities on a large scale. The yield of the prepared inorganic material is high and the catalytic activity is high.
[0075] In the embodiment of the present application, the loading amount of the inorganic material on the working electrode in the three-electrode electrolytic cell is 0.1-1 mg / cm 2 , current density is 10mA / cm 2 Under the conditions of , the overpotential of the inorganic material is below 240 mV, for example, 220-240 mV. This overpotential is lower than the overpotential of commercial iridium oxide material (about 270 mV). The lower overpotential can reflect that the inorganic material provided in the embodiment of the present application has more advantages in catalysis.
[0076] The embodiment of the present application further provides a catalyst, which includes the aforementioned inorganic material of the embodiment of the present application and a binder. The catalyst may be a composite material including the inorganic material and the binder.
[0077] The embodiments of the present application also provide applications of the above-mentioned inorganic materials and catalysts in fuel cells, water electrolysis, and other electrochemical technologies.
[0078] When the inorganic material or catalyst is used in the field of water electrolysis, it can be specifically used as an anode catalyst layer in electrolyzed water, that is, an anode catalyst for oxygen evolution reaction in water electrolysis. Wherein, the electrolyzed water can be proton exchange membrane (PEM) electrolyzed water. The inorganic material or catalyst can be specifically used in a PEM water electrolysis method or a PEM water electrolysis device. The inorganic material is specifically used as an anode catalyst for a PEM membrane electrode, which can exhibit excellent electrocatalytic activity and stability at a low loading of the precious metal iridium element, which helps to improve the operating efficiency of the PEM membrane electrode device and reduce costs.
[0079] When the inorganic material or catalyst is used in a fuel cell, it can be used in the anode catalyst layer of the fuel cell, mainly used to solve the reverse polarity phenomenon that occurs when the anode hydrogen supply in the fuel cell is insufficient, and play an anti-reverse polarity role. The reverse polarity phenomenon can cause severe corrosion of the anode catalyst in the membrane electrode of the fuel cell, thereby causing the attenuation of the fuel cell output performance. In actual commercial applications, in order to prevent the anode catalyst (Pt material loaded on carbon) of the fuel cell from undergoing carbon corrosion reaction in the reverse polarity phenomenon, a water electrolysis catalyst (such as the above-mentioned inorganic material or a catalyst containing the inorganic material in the embodiment of the present application) can be added to the anode catalyst of the membrane electrode of the fuel cell. The inorganic material can promote the oxygen evolution reaction on the anode catalyst layer instead of the carbon oxidation reaction of the platinum carbon catalyst to increase the generation rate of protons and electrons, protect the anode catalyst layer of the fuel cell, thereby effectively extending the reverse polarity time and improving the service life of the fuel cell. Among them, the fuel cell can be specifically a proton exchange membrane (PEM) fuel cell.
[0080] The present application also provides a membrane electrode, which includes a proton exchange membrane, and a catalyst layer on one side of the proton exchange membrane includes the inorganic material or the catalyst of the present application. The membrane electrode can be used in a fuel cell, a water electrolysis device, or other electrochemical devices.
[0081] Above Figure 1 An exemplary structure of a membrane electrode 10 is shown in a water electrolysis device. The membrane electrode 10 includes a proton exchange membrane 11, and an anode catalyst layer 12 and a cathode catalyst layer 13 located on opposite sides of the proton exchange membrane 11, wherein the anode catalyst layer 12 contains the above-mentioned inorganic material or the above-mentioned catalyst of the embodiment of the present application. Generally, the anode catalyst layer 12 contains the above-mentioned inorganic material and a binder of the embodiment of the present application.
[0082] In the embodiment of the present application, the loading amount of iridium element in the inorganic material in the membrane electrode 10 is 0.1-1 mg / cm 2 . When the iridium loading is low, the inorganic material can still exhibit excellent electrocatalytic activity and stability, which helps to improve the operating efficiency of the PEM membrane electrode device and reduce costs. In addition, a lower iridium loading can reduce the use of precious metal iridium in the membrane electrode 10, which is beneficial to reduce the catalyst cost. Specifically, the loading of iridium in the inorganic material in the membrane electrode 10 can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.32, 0.35, 0.38 or 0.4 mg / cm 2 .
[0083] In some implementation modes of the present application, Figure 1 As shown, a PEM water electrolysis device is provided, and the water electrolysis device 100 includes the above-mentioned membrane electrode 10, and the anode catalyst layer 12 and the cathode catalyst layer 13 of the membrane electrode 10 are respectively stacked with a gas diffusion layer and a bipolar plate current collector. Figure 1 Description.
[0084] Please continue to see Figure 1 The anode side of the membrane electrode 10 includes an anode gas diffusion layer 21 and an anode bipolar plate 22 from the inside to the outside, and the cathode side of the membrane electrode 10 includes a cathode gas diffusion layer 31 and a cathode bipolar plate 32 from the inside to the outside. The positive electrode of the external power supply is connected to the anode bipolar plate 22, and the negative electrode of the external power supply is connected to the cathode bipolar plate 32.
[0085] Each gas diffusion layer is located between the flow field and the catalyst layer on the bipolar plate. Its function is to support the catalyst layer, stabilize the structure of the membrane electrode, and has the function of transferring protons / heat / electricity. At the same time, it can provide multiple reaction channels such as gas, protons, electrons and water for the membrane electrode reaction. Among them, the anode gas diffusion layer 21 and the cathode gas diffusion layer 31 can be formed by conductive porous materials. Exemplarily, the anode gas diffusion layer 21 can be titanium felt, titanium mesh, etc.; the cathode gas diffusion layer 31 can be carbon paper, carbon fiber fabric, etc. A number of flow channel flow fields for water and gas transmission are respectively provided on the anode bipolar plate 22 and the cathode bipolar plate 32. In addition, the anode bipolar plate 22 can also be provided with an inlet end 221 for fluid inflow and a first outflow end 222 for fluid outflow, and the cathode bipolar plate 32 is provided with a first outflow end 321 for fluid outflow or gas discharge.
[0086] The working principle of the water electrolysis device 100 is as follows: the reactant (i.e., water) flows in from the inlet end 221 on the anode bipolar plate 22, diffuses to the anode gas diffusion layer 21 through the flow channel thereon, and penetrates and migrates to the surface of the anode catalyst layer 12. The water molecules are decomposed into hydrogen ions (H 2 O ) under the electrocatalytic action of the anode catalyst.+ , that is, protons), oxygen (O2) and electrons (e - ), where H + The electrons pass through the proton exchange membrane 11 and reach the surface of the cathode catalyst layer 13. The electrons are conducted to the cathode catalyst layer 13 through the external circuit. Under the action of the cathode catalyst, H + Combined with electrons, hydrogen (H2) is generated. In addition, the O2 generated on the anode side passes through the flow channel on the anode gas diffusion layer 21 and the anode bipolar plate 22, and is discharged to the oxygen storage tank through the first outflow terminal 222, and the H2 generated on the cathode side passes through the flow channel on the cathode gas diffusion layer 31 and the cathode bipolar plate 32, and is discharged to the hydrogen storage tank through the first outflow terminal 321.
[0087] In the embodiment of the present application, the loading amount of iridium element in the inorganic material in the membrane electrode is 0.1-1 mg / cm 2 The temperature of electrolyzed water is 80℃ and the current density is 2A / cm 2 Under the conditions, the electrolysis voltage of the water electrolysis device can be below 1.85V, for example, in the range of 1.7-1.85V.
[0088] The embodiments of the present application are further described below with reference to a plurality of embodiments.
[0089] Example 1
[0090] A method for preparing an inorganic material, comprising:
[0091] Weigh 10 g of KOH and 100 mg of IrCl3·3H2O (the molar ratio of KOH to Ir element in iridium salt is 629.6:1), put them into a corrosion-resistant silicon carbide crucible in turn, stir them evenly, put the crucible into a microwave reactor equipment, set the power of the microwave reaction equipment to 800 W, the reaction time to 30 min, and start the reaction equipment to start the reaction.
[0092] After the reaction is completed, after the crucible container containing the reaction materials is naturally cooled to room temperature, the crucible is taken out, and a large amount of deionized ultrapure water is added thereto to dissolve and wash away the unreacted raw materials, and solids are obtained by centrifugation or filtration separation, and the solids include inorganic materials; the solids are washed with water for multiple times-centrifuged or filtered until the pH of the washing liquid is neutral; then rinsed and purified with anhydrous ethanol for 3 times, and finally separated by centrifugation or filtration to obtain the purified inorganic material, and placed in a constant temperature vacuum drying oven at 60°C for drying, and then dried and stored at room temperature 25°C for standby use.
[0093] The inorganic material product obtained in Example 1 was characterized by scanning electron microscope (SEM). Figure 2As shown. Figure 2 It can be seen that the product has a three-dimensional cluster morphology, and each three-dimensional cluster is assembled by a number of iridium oxide nanosheets, with a three-dimensional self-supporting structure. Among them, the lateral size of the iridium oxide nanosheet is about 0.5-1.2μm, and the thickness is about 2-10nm. The particle size of the three-dimensional cluster structure is about 0.5μm-5μm.
[0094] The inorganic material product obtained in Example 1 was characterized by transmission electron microscope (TEM). Figure 3 As shown. Figure 3 It can be seen that the product has a significant lamellar structure, which can also help to explain that the product is a three-dimensional cluster assembled by nanosheets. Further, a single nanosheet was imaged and analyzed using a spherical aberration-corrected scanning transmission electron microscope (HAADF-STEM). , The results are as follows Figure 4 As shown in Figure a, the interplanar spacing of the high-resolution atomic image can correspond to the hexagonal crystal structure. The angle between adjacent crystal planes is 60°. Figure 4 The selected area electron diffraction (SAED) analysis of the A region in the a figure is performed by Fourier transform, and the results are as follows Figure 4 A in the figure * As shown in the inset, the pattern spots of electron diffraction in this selected area are consistent with the crystal plane index of the hexagonal crystal structure, such as The phase calibration is consistent.
[0095] In addition, selected area electron diffraction analysis was performed on multiple other regions of a single iridium oxide nanosheet, and the electron diffraction spectrum of the obtained selected area electron diffraction pattern was calibrated. Figure 4 Middle A * The small picture is similar. According to the Bragg law of electron diffraction of crystals, the diffraction pattern of a single crystal is a spot pattern, and the diffraction pattern of a polycrystal is a ring pattern. *The selected area electron diffraction pattern of the nanosheet in the small picture only has bright lattices, so the nanosheet is a single crystal structure. Further lattice measurement and analysis and calibration of the diffraction bright spots around the transmission spot near the center of the electron diffraction pattern show that the geometric shape of the basic unit expressing the symmetry of the diffraction pattern is a regular hexagon, and the index calibration results of the six diffraction points that constitute the regular hexagon are consistent with the crystal plane index of the hexagonal crystal phase structure, and the reciprocal lattices of the crystal planes of the two are also basically the same, indicating that the nanosheet sample is a single crystal iridium oxide in the hexagonal crystal phase.
[0096] In addition, detailed spherical aberration electron microscopy characterization of individual nanosheets that make up the nanocluster inorganic material revealed that at higher magnifications, a single nanosheet is composed of a large number of atomic-layer-level ultra-thin sheets stacked face to face (e.g. Figure 4 The interlaminar spacing between the atomic layer ultra-thin sheets is about 0.686nm, which is consistent with the crystal structure simulation diagram of the material (as shown in Figure b). Figure 4 The theoretical interlayer spacing obtained in Figure c) is consistent with the experimental test results of subsequent XRD, so the three-dimensional cluster structure inorganic material prepared in this embodiment is self-assembled by hexagonal crystalline iridium oxide sheets. Figure 4 Figure c is a simulation diagram of the unit cell structure of iridium oxide nanosheet material based on experimental characterization test results. The figure shows that the prepared iridium oxide nanosheet is a hexagonal Bragg unit cell, and its three-dimensional periodic structure is composed of octahedral skeletons composed of iridium atoms and oxygen atoms connected by mutual common edges, and is periodically extended and extended to form an iridium oxide layered nanosheet structure. Among them, Figure 4 The small red dots in the upper image of Figure c represent oxygen atoms, and the areas indicated by dotted arrows in the lower image are oxygen atoms.
[0097] Furthermore, the inorganic material product of Example 1 was subjected to powder X-ray diffraction (XRD) analysis and testing, and the obtained spectrum was as follows: Figure 5 shown. Figure 5 In the XRD spectrum, the peaks of 2θ at 33.4°, 36°, and 43° correspond to the crystal plane diffraction peaks of the hexagonal phase structure of iridium oxide nanosheets. This result is consistent with the crystal plane calibrated by the selected area electron diffraction pattern. These are different from the 2θ diffraction peaks of iridium oxide nanoparticles at 28°, 34.7°, 54°, etc. of the traditional tetragonal phase. In addition, the diffraction peaks of 2θ at 13°, 26°, 39°, 52°, 65°, 78°, etc. correspond to the diffraction peaks of different interlayer spacings between iridium oxide nanosheets in the three-dimensional cluster structure. Figure 6 This is a test chart of the specific surface area of the inorganic material prepared in Example 1 of the present application measured by the nitrogen adsorption method. Figure 6 It can be seen that the inorganic material exhibits a large surface area, which can reach 79.7m 2 / g.
[0098] Furthermore, the inorganic material prepared in Example 1 of the present application was subjected to a polarization test of a three-electrode oxygen evolution reaction, and a platinum-carbon electrode or carbon paper loaded with the inorganic material in Example 1 was used as a working electrode (the loading amount of the inorganic material on the working electrode was 0.5 mg cm -2 ), a graphite carbon rod was used as the counter electrode, a saturated calomel electrode was used as the reference electrode, and a 0.5 mol / L sulfuric acid solution was selected as the electrolyte to assemble a three-electrode electrolytic cell. The electrochemical data of the three-electrode electrolytic cell were tested by linear sweep voltammetry. The test results are as follows: Figure 7 As shown. Figure 7 It can be seen that the inorganic material in Example 1 as a catalyst for the three electrodes is 10 mA / cm 2 At a current density of , its catalytic overpotential is only 220 mV, which is much lower than the commercial IrO2 catalyst (about 270 mV), showing good electrocatalytic performance.
[0099] Preparation of membrane electrodes and devices and device performance testing:
[0100] The inorganic material prepared in Example 1 is used as an anode catalyst, and is sprayed or transferred onto one side (i.e., the anode side) of a proton exchange membrane (specifically, Nafion 115 membrane of DuPont) to form an anode catalyst layer, and a cathode catalyst layer is formed on the other side (i.e., the cathode side) of the proton exchange membrane to obtain a membrane electrode. Specifically, a commercial platinum-carbon catalyst Pt / C is used as a cathode catalyst.
[0101] The membrane electrode is assembled with the anode / cathode gas diffusion layer, the sealing gasket, the bipolar plate current collector, the end plate, etc. Figure 1 The PEM water electrolysis device shown in FIG. 1 was tested for water electrolysis performance at 80° C. The test results are shown in FIG. Figure 8 and Fig. 9 As shown. Among them, Figure 8 , Fig. 9 The polarization test curves and electrochemical stability curves of the PEM water electrolysis device prepared by using the inorganic material of Example 1 as the anode catalyst of the membrane electrode are summarized respectively. Figure 8 and Fig. 9 In the figure, “40wt% Pt / C” means that the mass proportion of Pt in the platinum-carbon catalyst is 40wt%.
[0102] from Figure 8 It can be seen that the Ir element loading of the inorganic material in Example 1 of the present application as the anode catalyst in the membrane electrode is as low as 0.17 mg·cm -2 Under the conditions of 80℃ and 2A / cm 2The electrolysis voltage under this condition is only 1.78V, showing excellent membrane electrode device performance, which also reflects that the inorganic material of Example 1 has high catalytic activity as an anode catalyst. Fig. 9 It can be seen that the Ir element loading of the inorganic material in Example 1 of the present application as the anode catalyst in the membrane electrode is 0.857 mg·cm -2 Under the conditions of 80℃ and 1500mA / cm 2 (i.e. 1.5A / cm 2 ) for more than 500 h, no device performance degradation was observed, indicating that the anode catalyst has good stability.
[0103] Example 2
[0104] A method for preparing an inorganic material, which is mainly different from Example 1 in that the amount of the raw material IrCl3·3H2O is changed from 100 mg to 130 mg. At this time, the molar ratio of KOH to the Ir element in the iridium salt is 484.34:1.
[0105] The inorganic material product obtained in Example 2 was characterized by SEM, TEM, selected area electron diffraction, XRD, etc., and the results were similar to those in Example 1. The inorganic material was also a three-dimensional cluster structure assembled from single-crystal iridium oxide nanosheets in the hexagonal phase.
[0106] Furthermore, the performance of the PEM water electrolysis device made of the inorganic material of Example 2 as the anode catalyst of the membrane electrode was tested. The results showed that the Ir element loading in the membrane electrode of the inorganic material of Example 2 was 0.385 mg·cm -2 , electrolysis at 80°C, with a current density of 2A / cm 2 The electrolysis voltage is 1.8 V. This indicates that the inorganic material prepared in Example 2 exhibits a high OER catalytic activity in PEM water electrolysis, far exceeding the current commercial IrO2.
[0107] Example 3
[0108] A method for preparing an inorganic material, which is mainly different from Example 1 in that the amount of the raw material IrCl3·3H2O is changed from 100 mg to 60 mg (at this time, the molar ratio of KOH to the Ir element in the iridium salt is 1049.4:1), the power of the microwave reaction is 500 W, and the reaction time is still 30 min.
[0109] The inorganic material product obtained in Example 3 was subjected to characterization and analysis such as SEM, TEM, selected area electron diffraction, and XRD, and the results were similar to those in Example 1, indicating that the inorganic material was a three-dimensional cluster structure assembled from single-crystal iridium oxide nanosheets in a hexagonal phase.
[0110] Furthermore, the performance of the PEM water electrolysis device made of the inorganic material of Example 3 as the anode catalyst of the membrane electrode was tested. The results showed that the Ir element loading in the membrane electrode of the inorganic material of Example 3 was 0.4 mg·cm -2 , electrolyze water at a temperature of 80°C, and the PEM water electrolysis device can achieve a current density of 2A / cm 2 The electrolysis voltage is 1.82V.
[0111] Example 4
[0112] A method for preparing an inorganic material, which is mainly different from Example 1 in that the power of the microwave reaction is 1000 W and the reaction time is 5 min.
[0113] Fig.10 is a SEM photo of the inorganic material obtained in Example 4. Fig.10 It can be observed that the inorganic material has a three-dimensional cluster morphology, and each three-dimensional cluster is assembled from a plurality of iridium oxide nanosheets. Among them, the lateral size of the nanosheet is about 0.2-1.0 μm, and the thickness is about 1-5 nm. The particle size of the three-dimensional cluster is about 0.3-1.5 μm. The inorganic material obtained in Example 4 was further characterized by TEM, selected area electron diffraction, XRD, etc., and the results were similar to those in Example 1, both indicating that the nanosheets constituting the three-dimensional cluster structure are single crystal iridium oxide nanosheets in the hexagonal phase.
[0114] The performance of the PEM water electrolysis device made of the inorganic material of Example 4 as the anode catalyst of the membrane electrode was tested. The results showed that the Ir element loading in the membrane electrode of the inorganic material of Example 4 was 0.2 mg·cm -2 , electrolyze water at a temperature of 80°C, and the current density of the PEM water electrolysis device reaches 2A / cm 2 The electrolysis voltage is 1.8 V. This indicates that the inorganic material prepared in Example 4 exhibits a high OER catalytic activity in PEM water electrolysis, far exceeding the current commercial IrO2.
[0115] Example 5
[0116] A method for preparing an inorganic material, which is mainly different from Example 1 in that the power of the microwave reaction is 900 W and the reaction time is 20 min.
[0117] The inorganic material product obtained in Example 5 was subjected to characterization and analysis such as SEM, TEM, selected area electron diffraction, and XRD, and the results were similar to those in Example 1. The inorganic material included a three-dimensional cluster structure assembled from single-crystalline iridium oxide nanosheets in a hexagonal phase.
[0118] Furthermore, the performance of the PEM water electrolysis device made of the inorganic material of Example 5 as the anode catalyst of the membrane electrode was tested. The results showed that the Ir element loading in the membrane electrode of the inorganic material of Example 5 was 0.3 mg·cm -2 , electrolyze water at a temperature of 80°C, and the PEM water electrolysis device can achieve a current density of 2A / cm 2 The electrolysis voltage was 1.81V.
[0119] Example 6
[0120] A method for preparing an inorganic material, which is mainly different from Example 1 in that the raw material IrCl3·3H2O is replaced by iridium nitrate.
[0121] The inorganic material product obtained in Example 6 was subjected to SEM ( Fig.11 ), TEM, selected area electron diffraction, XRD and other characterization analyses, the results of which are similar to those of Example 1, the inorganic material includes a three-dimensional cluster structure assembled from single-crystalline iridium oxide nanosheets in a hexagonal phase.
[0122] Furthermore, the performance of the PEM water electrolysis device made of the inorganic material of Example 6 as the anode catalyst of the membrane electrode was tested. The results showed that the Ir element loading in the membrane electrode of the inorganic material of Example 6 was 0.3 mg·cm -2 , electrolyze water at a temperature of 80°C, and the PEM water electrolysis device can achieve a current density of 2A / cm 2 The electrolysis voltage is 1.82V.
[0123] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.
[0124] Comparative Example 1
[0125] A method for preparing an inorganic material, which is mainly different from Example 1 in that the power of the microwave reaction is 1100 W and the reaction time is 60 min.
[0126] The product sample obtained in Comparative Example 1 was characterized by SEM, and the results were as follows: Fig.12 As shown. Fig.12 It can be observed that the product is aggregated nanoparticles with a particle size of about 50-200 nm. This may be due to the fact that the energy of the microwave reaction used in Comparative Example 1 (the product of the power and time of the microwave reaction in Comparative Example 1 is 60000 W·min) is too large.
[0127] In addition, the performance of the PEM water electrolysis device made by using the product of Comparative Example 1 as the anode catalyst of the membrane electrode was tested. The results showed that the loading of Ir element in the membrane electrode in the product was 0.5 mg cm -2, electrolyze water at a temperature of 80°C, and the PEM water electrolysis device can achieve a current density of 2A / cm 2 The electrolysis voltage is 1.85 V. It can be seen that when the Ir loading of the product of Comparative Example 1 is higher than that of the inorganic materials of Examples 1, 4, and 5 of the present application, under the same temperature and water electrolysis current density, the water electrolysis voltage is still higher than that of the present application, which indicates that the catalytic activity of the inorganic materials provided in the present application is relatively strong.
[0128] The above only expresses several exemplary embodiments of the present application, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present application. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be based on the attached claims.
[0129] It should be understood that the first, second and various numerical numbers involved in this document are only distinguished for the convenience of description and are not used to limit the scope of the present application.
[0130] In this application, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0131] In this application, "at least one" means one or more, and "more than one" means greater than or equal to two. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
Claims
1. An inorganic material, characterized in that The inorganic material includes iridium oxide nanomaterial, and the iridium oxide nanomaterial has a hexagonal crystal phase structure.
2. The inorganic material according to claim 1, characterized in that The crystal structure of the iridium oxide nanomaterial includes iridium oxygen octahedrons, and the iridium oxygen octahedrons are connected to form the hexagonal crystal phase structure.
3. The inorganic material according to claim 1 or 2, characterized in that In the iridium oxide nanomaterial, there are two crystal planes with an angle of 59.5°-60.5°.
4. The inorganic material according to any one of claims 1 to 3, characterized in that In the XRD spectrum of the inorganic material, there are crystal plane diffraction peaks at 2θ of 32.9°-33.9° and 35.5°-36.5°.
5. The inorganic material according to any one of claims 1 to 4, characterized in that The inorganic material contains a single crystal iridium oxide nanomaterial having the hexagonal crystal phase structure.
6. The inorganic material according to any one of claims 1 to 5, characterized in that The iridium oxide nanomaterial comprises iridium oxide nanosheets.
7. The inorganic material according to claim 6, characterized in that The thickness of the iridium oxide nanosheet is 0.2-50 nm; the lateral size of the iridium oxide nanosheet is 0.01 μm-10 μm.
8. The inorganic material according to any one of claims 1 to 7, characterized in that At least a number of the iridium oxide nanomaterials are assembled into a three-dimensional cluster structure.
9. The inorganic material according to claim 8, characterized in that The average particle size of the three-dimensional cluster structure is 0.03 μm-20 μm.
10. The inorganic material according to any one of claims 1 to 9, characterized in that The specific surface area of the inorganic material is 50-100m 2 / g.
11. The inorganic material according to any one of claims 1 to 10, characterized in that In the inorganic material, the mass percentage of the iridium oxide is 100%.
12. The inorganic material according to any one of claims 1 to 10, characterized in that The inorganic material further comprises one or more of platinum oxide and ruthenium oxide.
13. The inorganic material according to claim 12, characterized in that In the inorganic material, the mass percentage of the iridium oxide is 50-95%.
14. The inorganic material according to any one of claims 1 to 13, characterized in that: The loading of the inorganic material on the working electrode in the three-electrode electrolytic cell is 0.1-1 mg / cm 2 , current density is 10mA / cm 2 Under the conditions of , the overpotential of the inorganic material is below 240mV.
15. A method for preparing an inorganic material, characterized in that: The following steps are involved: Placing a reaction material comprising a solid alkali metal hydroxide and a solid iridium salt in a microwave reaction device for microwave reaction to obtain a reaction material; wherein the product of the power in watts and the reaction time in minutes in the microwave reaction is in the range of 3000-30000; The obtained reaction materials are dispersed in water, and solids are obtained by solid-liquid separation. The obtained solidified material is an inorganic material; wherein the inorganic material comprises iridium oxide nanomaterial, and the iridium oxide nanomaterial has a hexagonal crystal phase structure.
16. The preparation method according to claim 15, characterized in that: The power of the microwave reaction is 500-1000W, and the reaction time is 5-60min.
17. The preparation method according to claim 15 or 16, characterized in that: The molar ratio of the alkali metal hydroxide to the iridium element in the iridium salt is (100-5000):
1.
18. A catalyst, characterized in that The catalyst comprises the inorganic material according to any one of claims 1 to 14 or the inorganic material prepared by the preparation method according to any one of claims 15 to 17, and the catalyst further comprises a binder.
19. Use of the inorganic material according to any one of claims 1 to 14 and the catalyst according to claim 17 in fuel cells, water electrolysis, and other electrochemical technologies.
20. The use according to claim 19, characterized in that The inorganic material or the catalyst is used in the anode catalyst layer in the water electrolysis or in the anode catalyst layer of the fuel cell.
21. A membrane electrode, characterized in that: The membrane electrode comprises a proton exchange membrane, and an anode catalyst layer and a cathode catalyst layer arranged on opposite sides of the proton exchange membrane, wherein the anode catalyst layer comprises the inorganic material according to any one of claims 1 to 14, or the catalyst according to claim 18.
22. The membrane electrode according to claim 21, characterized in that The loading amount of iridium element in the inorganic material in the membrane electrode is 0.1-1 mg / cm 2 .
23. A water electrolysis device, characterized in that: The water electrolysis device comprises the membrane electrode as described in any one of claims 21-22, wherein a gas diffusion layer and a bipolar plate current collector are sequentially stacked on opposite sides of the membrane electrode.
24. The water electrolysis device according to claim 23, characterized in that The loading amount of iridium element in the inorganic material in the membrane electrode is 0.1-1 mg / cm 2 , current density is 2A / cm 2 Under the conditions of , the electrolysis voltage of the water electrolysis device is below 1.85V.